An adaptive energy management strategy for airports to achieve carbon neutrality by 2050 via waste, wind, and solar power - Goh, Hui Hwang; Suo, Wenxuan; Liang, Xue; Zhang, Dongdong; Dai, Wei; Kurniawan, Tonni Agustiono; Goh, Kai Chen (Frontiers in Energy Research, 2024)
After the border lockdown, global traffic has returned, making green airports a government goal to reach carbon neutrality by 2050. Sustainable aviation fuel (SAF) use for commercial aircraft alone won't help achieve net-zero emissions (NEZ). An independent renewable energy supply system at airports is urgently needed to implement green airports worldwide. This study develops a renewable energy power supply system that integrates wind, photovoltaic (PV), and waste-to-energy (WTE) sources to investigate a new adaptive model predictive control (MPC) energy management strategy based on airport operational characteristics. Simulations of Copenhagen Airport’s energy programme confirmed this energy management strategy’s feasibility. Energy management scenarios for two typical summer and winter load days were simulated for case studies. Field data from Copenhagen was used for simulation analysis, and experimental modelling of the airport’s energy scheme proved the energy management program’s practicality. The simulations show that Copenhagen airport renewable energy generates half of its electricity in winter and 81.0% in summer. A total operating cost of USD 36,087.83/day in summer and USD 102,061.20/day in winter is needed to reduce carbon emissions by 41.19 Mt/day in summer and 43.96 Mt/day in winter. This approach should help deploy green airports worldwide and reach carbon neutrality by 2050.